Vulnerabilidade dos sistemas GNSS a ataques do tipo Spoofing - Machado, Vinícius (2019)
The vulnerability of the GNSS constellation extends beyond blocking and signal loss to fake attacks, where communication signal spoofs are generated to manipulate the position, speed, and information a receiver receives. Considering that several systems are part of the GNSS constellation, it was necessary to carry out a study of the systems and verify how each system behaves when receiving a spoofing attack. The main systems, GPS, GLONASS, Galileo and Beidou, were analyzed in relation to communication frequencies and their methods to avoid a spoofing attack. The data from some systems because they are more used and even better known, are found in open documents available on the Internet, while others less known, are obtained through studies conducted at universities. The combination of known signal structure and data bit predictability makes GNSS civil signals an easy target for spoofing attacks. The paper analyzes the countermeasures of each system, whether each one has a specific type or if they all use the same pattern of defense and in that, an approach to some existing countermeasures.